‘Juntando a fome com a vontade de comer’: discussion on the implementation of cycle infrastructure as a way to promote social equity and sustainability in Prado, Bahia, Brazil. - Emlinger, Ana Mesquita; de Cássia-Bruno, Rita (Revista Geográfica de América Central., 2018)
Cycling in urban mobility is a beneficial habit of active transport. Researches affirm that urban cycling is associated not only with the availability of cycle infrastructure, favorable topography, urban form and mild climate, but mainly to the habit of pedaling. In Prado, a small historical and tourist city in northeastern Brazil, the bicycle is used by residents as one of the main means of transportation, despite the absolute lack of cycling infrastructure in the city. This article focuses on the possibilities of implementing a cycle network in this locality. A survey of local residents was conducted to understand cyclists' profile, patterns and travel frequency, as well as specific problems faced by cyclists in the city. This article discusses the preliminary results of this research. Both cyclists and non-cyclists who participated in the research agree that the implementation of cycling infrastructure would serve not only as a motivator for incorporating the bicycle as a means of daily transportation, but would impact the increase of frequency for those who occasionally use it. A cycle network in Prado would benefit the common resident throughout the year as well as tourists visiting the city. This approach, by diverging from the tradition of urban improvements often aimed at the central areas of American and Brazilian cities, becomes a good example of social equity, and sustainability.